MASJID SEBAGAI MEDIA DERADIKALISASI DI INDONESIA - Munawir Aziz (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2013)
The mosque becomes the arena for power struggling between ideology and political interests in terms of identity negotiation among Islamic mainstreams in Indonesia. The mosque is also considered to be the important part in the context of religious movement and symbol of the collective identity. Then, the conflict of interest in terms of its philosophy and authority of the mosque becomes inevitable issue. Such phenomenon actually emerged from the reality of the growing diversity of religious models in Indonesia, particularly in the corpus of Islamic religion. The emergence of radical movements in the Indonesian Muslim society becomes an important mark that changes social structures of religion in the country. On one side, the issue of caliphate or Islamic state is used as a weapon of discourse that facilitates the involvement of any party in the political system. Consequently, it leads to the interest ​​contestation in a broad sense of mosque. The mosque became the center of political interest; it turns as a commodity to support the representatives. So, this paper will explore the genealogy of radicalism in Indonesia that investigates the root of interest contestation in the "public area" of mosque. Furthermore, identity negotiation perspective and "public sphere" of Habermas will be used to analyze the models of power struggle in the mosque. At the end, the writer offers deterrorization and de-radicalization strategies for the mosque communities by making the mosque and community as a "habitus" in the framework of Boudieu.